PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA PERAWAT HONORER PADA RUMAH SAKIT UMUM DAERAH REJANG LEBONG - Muhammad Dioba Sanjaya; Marliza Ade Fitri (UM. Bengkulu, 2022)
This study aims to determine the effect of compensation and motivation on the performance of honorary nurses at the Rejang Lebong Regional General Hospital. This type of research uses quantitative methods, the object of this research is the Honorary Nurse at the Rejang Lebong Regional General Hospital with the sampling method, namely the total sampling technique. The number of respondents in this study were 77 people. In this research, the author uses data collection methods by means of observation, interviews and distributing questionnaires or questionnaires. By using data analysis techniques using Instrument Test, namely Validity Test and Reliability Test, Classical Assumption Test, namely Multicollinearity Test, Normality Test. and Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Coefficient of Determination (R2), and Hypothesis Testing, namely t-test and f-test. The results of this study can be concluded that the compensation variable has a partially significant effect on the Performance of Honorary Nurses at the Rejang Lebong Regional General Hospital, motivation has a partially significant effect on the Performance of Honorary Nurses at the Rejang Lebong Regional General Hospital, and compensation and motivation have a simultaneous significant effect on Performance of Honorary Nurses at the Rejang Lebong Regional General Hospital. Keywords: Compensation, Motivation, Nurse Performance